The Proof of Occurrence between the Ashʿarites and the Athari School - Tarteer, Khalid (Jordan Journal of Islamic Studies, 2025)
This research aims to clarify the meaning and significance of the proof of occurrence (dalil al-huduth) according to the Ashʿarites in proving the existence of Allah Almighty, and to present the response given by the Athari or Hadith school regarding their method of inference. The research problem is represented by the following questions: What is the proof of occurrence that the Ashʿarites used to argue for the existence of Allah Almighty? What is the proof of innate disposition (dalil al-fitrah) that the Athari school used to prove the existence of Allah Almighty? How did the Athari school critique the Ashʿarites regarding the proof of occurrence? By adopting the analytical deductive method and the critical comparative method, the research found that the Ashʿarite scholars paid great attention to the proof of occurrence in affirming the existence of Allah Almighty. They typically began their theological works by discussing this proof, formulating it according to the rules of the logicians, and supporting it with verses from the Qur’an and Prophetic traditions. On the other hand, the Athari or Hadith school did not focus on the proof of occurrence or discuss it; they viewed the knowledge of Allah Almighty as an innate, natural matter that does not require rational proof but rather indication. They responded to the Ashʿarites by asserting that the approach of the Prophets was to call to the oneness of Allah Almighty, not to provide logical proof of His existence as done by the logicians.